Training primary care clinicians in motivational interviewing: A comparison of two models. Issue 1 (January 2015) - Fu, Steven S.; Roth, Craig; Battaglia, Catherine T.; Nelson, David B.; Farmer, Melissa M.; Do, Tam; Goldstein, Michael G.; Widome, Rachel; Hagedorn, Hildi; Zillich, Alan J.
Highlights Few health professionals utilize motivational interviewing (MI) as part of routine practice due to lack of expertise and training. This study evaluated two training models for motivational interviewing and tobacco cessation counseling for primary care clinicians. Using enhancement strategies (i.e., MI clinical champions as peer coaches and telephone interactions with simulated patients) to supplement or boost initial training workshops is feasible in busy primary care settings. Booster training sessions improve proficiency of MI training programs for primary care clinicians.